PENGARUH KOMPETENSI DAN LOYALITAS PEGAWAI TERHADAP KUALITAS PELAYANAN DI DINAS PENDIDIKAN KOTA SUKABUMI - Rita Stiaharti (Mimbar Administrasi Mandiri, 2022)
The main problem in this research is the low quality of service which according to the researcher's observations is caused by the competence and loyalty of employees who are not yet optimal. On the basis of these thoughts and considerations, the approach taken in this study uses a quantitative method using a questionnaire instrument. Based on the characteristics of the data used, this study uses a quantitative research approach. The analytical technique used is descriptive statistical technique which functions to classify data, work on, conclude, explain and present the processed results. It aims to make a pattern of cause and effect relationship between the value of a variable with other variables. The infrensial test was carried out through validity and reliability tests as well as classical assumption tests. Hypothesis testing is done through regression analysis. Shows that Service Quality is influenced by Employee Competence and Loyalty, either partially or simultaneously. Partially the quality of service is influenced by competence by 73.2% and employee loyalty by 61.8%. The conclusion in this study is that the Competence and Loyalty of Employees partially or simultaneously have an influence on the Quality of Service at the Dinas Pendidikan Kota Sukabumi.